2020
DOI: 10.1111/jpn.13404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the effective microorganisms (EM) on performance, intestinal morphology and gene expression in the jejunal mucosa of pigs fed different diets

Abstract: The aim of the study was to determine the influence of the effective microorganisms (EM) on performance parameters, intestinal morphology and gene expression in the jejunal mucosa in pigs under different feeding regimes. The study group comprised of 150 piglets divided into three feeding groups: C, E1 and E2. Feeding groups included: C—standard fodder, blend with a full share of post‐extracted soy meal, E1—in the phase I of fattening: pea and lupin/soybean 50/50%; in the phase II of fattening: pea and lupin/so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Our results also include interesting observations concerning goblet cells in the jejunum. We observed higher goblet cell proliferation in the CP group, in contrast to Abdel-Aziz et al [ 27 ] in Nile tilapia and Reszka et al [ 28 ] in pigs after EM addition. In our opinion, an increased number of goblet cells is a consequence of pathogen stimuli and causes more protective mucus.…”
Section: Discussioncontrasting
confidence: 97%
“…Our results also include interesting observations concerning goblet cells in the jejunum. We observed higher goblet cell proliferation in the CP group, in contrast to Abdel-Aziz et al [ 27 ] in Nile tilapia and Reszka et al [ 28 ] in pigs after EM addition. In our opinion, an increased number of goblet cells is a consequence of pathogen stimuli and causes more protective mucus.…”
Section: Discussioncontrasting
confidence: 97%
“…Thus, great efforts have been made to improve the nutritive values of feeds to enhance growth performance and health of animals ( Ahmad et al, 2018 ). Probiotics, defined as “live microorganisms”, are one of the major feed additives routinely being used in animal production for decades due to the conferred health benefits to the host when administered in an adequate amount ( FAO, 2002 ; Markowiak & Liewska, 2018 ; Iriti et al, 2019 ; Reszka et al, 2020 ). For poultry, probiotics could improve feed intake and digestion efficiency by increasing the activity of digestive enzymes, keep the balance of bacteria in gastrointestinal (GI) tract, promote the gut integrity and thus improve the growth performance and health of birds ( Johnson et al, 2018 ; Soomro et al, 2019 ; Hack et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increased concentrations of cytokines IL-4, IL-10 and TGF-β, and of immunoglobulins in colostrum and milk, proved the immunoregulatory effect of EM ® Bokashi on Th2 cells, leading to increased expression of regulatory T cells and the polarization of the immune response from Th1 to Th2 [ 16 ]. The results of yet other study indicated that EM ® Bokashi supplementation had a positive effect on the morphological characteristics of porcine jejunum and caused an increase in the gene expression related to the key metabolic pathways of the gastrointestinal tract [ 17 ].…”
Section: Introductionmentioning
confidence: 99%